Publics and their health Historical problems and perspectives - Mold, Alex; Clark, Peder; Elizabeth, Hannah (Manchester University Press, 2023)
The nature of the relationship between publics and their health has long been a concern for those seeking to improve collective and individual health. Attempts to secure the health of the population of any given place are one of the oldest forms of governmental action. Whether it be providing clean water or preventing the spread of disease, such efforts require the involvement of the publics these measures are designed to protect. Despite its importance, surprisingly little attention has been paid to who or what the 'public' of public health consisted of. This collection addresses this gap by considering 'who' the public of public health was in an array of places and around a variety of public health problems. Ranging across Europe and North and South America, and from the interwar period to the near present, this book explores the construction of 'problem publics' to deepen our understanding of the 'who' of public health. This book offers detailed case studies of the making of 'problem' publics and public health problems in different places and at different times. By placing examples of the construction of problem publics in contexts as diverse as the USA in the interwar period, East Germany in the 1980s and contemporary Argentina, this collection identifies what is general and what is specific to the processes that make certain kinds of publics appear problematic. In the wake of the COVID-19 pandemic, this volume offers fresh insights into the nature of public health problems, practices and publics.